RANCANG BANGUN APLIKASI PERHITUNGAN GAJI KARYAWAN BERDASARKAN PRESENSI KARYAWAN PADA PT EPSINDO JAYA PRATAMA PRABUMULIH BERBASIS WEB - Al Fando; Iwan Setiawan; Yeni Yuliana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
PT. Epsindo Jaya Pratama Prabumulih is a company engaged in the manufacturing and development of Electric Submersible Pump Systems (ESPS) and Horizontal pumping systems (HPS). This equipment is widely used in the oil and gas mining industry both in Indonesia and abroad. The company is also very aware of the importance of quality human resource (HR) services to encourage company development, so it must improve its employee information system to process employee salary calculations based on employee attendance.However, the problem with this in the HR department is that it is still difficult to make employee salary calculation reports, they still use manual calculations for employee salaries, namely inputting them in Microsoft Exel. The purpose of the research is how to design and build an application for calculating employee salaries based on employee presence at PT Epsindo Jaya Pratama Prabumulih Web-Based. The research method uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and literature study. The type of data consists of qualitative data and data sources consist of primary and secondary data. The device development method uses the waterfall method. System design tools used are use case diagrams, class diagrams, activity diagrams. This application was built using a website with the PHP programming language and MySQL database, and to print reports using a pdf component.